FOXP2 is not a major susceptibility gene for autism or specific language impairment. - Newbury, D; Bonora, E; Lamb, J; Fisher, S; Lai, C; Baird, G; Jannoun, L; Slonims, V; Stott, C; Merricks, M; Bolton, P; Bailey, A; et al. (2002)
The FOXP2 gene, located on human 7q31 (at the SPCH1 locus), encodes a transcription factor containing a polyglutamine tract and a forkhead domain. FOXP2 is mutated in a severe monogenic form of speech and language impairment, segregating within a single large pedigree, and is also disrupted by a translocation in an isolated case. Several studies of autistic disorder have demonstrated linkage to a similar region of 7q (the AUTS1 locus), leading to the proposal that a single genetic factor on 7q31 contributes to both autism and language disorders. In the present study, we directly evaluate the impact of the FOXP2 gene with regard to both complex language impairments and autism, through use of association and mutation screening analyses. We conclude that coding-region variants in FOXP2 do not underlie the AUTS1 linkage and that the gene is unlikely to play a role in autism or more common forms of language impairment.